2021
DOI: 10.1039/d1lc00651g
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive and label-free identification of human natural killer cell subclasses by biophysical single-cell features in microfluidic flow

Abstract: Natural Killer (NK) are indicated as favorite candidates for innovative therapeutic treatment and are divided in two subclasses: immature regulatory NK CD56bright and mature cytotoxic NK CD56dim. Therefore, the ability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The machine learning (ML) approach was carried out with a Matlab (R2020b, MathWorks) routine to classify circulating monocytes from macrophages, as well as the main subtypes of macrophage phenotypes (M0, M1 and M2) based on their biophysical properties retrieved from optical cell signatures. Several classification methods were set up with operational parameters chosen based on previous experiments of our working group [ 31 , 33 ]. For ML training, a randomly chosen subset of data (all donors) was used, followed by testing classification accuracy on the remaining data (all donors), while the classification accuracy was measured by fivefold cross-validation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The machine learning (ML) approach was carried out with a Matlab (R2020b, MathWorks) routine to classify circulating monocytes from macrophages, as well as the main subtypes of macrophage phenotypes (M0, M1 and M2) based on their biophysical properties retrieved from optical cell signatures. Several classification methods were set up with operational parameters chosen based on previous experiments of our working group [ 31 , 33 ]. For ML training, a randomly chosen subset of data (all donors) was used, followed by testing classification accuracy on the remaining data (all donors), while the classification accuracy was measured by fivefold cross-validation.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, measurements are realized using a lab-on-a-chip approach permitting the measurement of living cells in suspension, which furthermore are collectable and re-usable for other diagnostic investigations or therapeutic approaches. We have already investigated such optical signature of other human cell types and subtypes [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the viscoelastic fluid (polyethylene oxide, MW = 4 MDa) forces of the resulting fluid, tuned with the flow velocity and geometry of the channel, result in cellular alignment maintained throughout the readout channel. [19,22] Note that cells can be recovered for further cell studies.…”
Section: Microfluidic Devicementioning
confidence: 99%
“…In more detail, a microfluidic device combined with an optical single cell investigation readout (combination of forward-and side-direction) was used for data recording of different cell classes. [19][20][21] Machine learning uses the scattering information as input to predict the searched for cell types. A prediction model was trained for a set of human peripheral blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al compared flow cytometry and ECIS based cytotoxicity assays and found slightly discrepant results, however they used different target cells [310]. NK cell subpopulations (the mature cytotoxic CD56dim and the regulatory CD56bright) can be distinguished in the microfluidic system designed by Dannhauser et al based on their light scattering properties with the help of machine learning [311]. Examples of labelfree characterization of lymphocytes are shown in Fig.…”
Section: Lymphocytesmentioning
confidence: 99%